2018
DOI: 10.1016/j.bjm.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of nanoemulsions encapsulating oregano (Origanum vulgare) essential oil: in vitro study and application in Minas Padrão cheese

Abstract: The objective of this study was to evaluate the antifungal activity of nanoemulsions encapsulating essential oil of oregano (Origanum vulgare), both in vitro and after application on Minas Padrão cheese. Nanodispersions were obtained by the phase inversion temperature method. Cladosporium sp., Fusarium sp., and Penicillium sp. genera were isolated from cheese samples and used to evaluate antifungal activity. Minimal inhibitory concentrations of non-encapsulated and encapsulated oregano essential oil were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(64 citation statements)
references
References 44 publications
4
56
0
4
Order By: Relevance
“…The main components of oregano essential oil (OEO) (Origanum vulgare L.) are carvacrol and thymol, which together represent up to 85% of its composition (Burt, 2004). Oregano essential oil has been associated with antifungal (Bedoya-Serna et al, 2018), antibacterial, and antioxidant activity in vitro (Gandra et al, 2013) and in vivo (Zanini et al, 2013;Ri et al, 2017), stimulation of enzyme secretion (He et al, 2017), and modulation of microbial colonization of the gastrointestinal tract and intestinal morphology (Dias et al, 2015;He et al, 2017). However, reports of its effects on the performance and carcass characteristics of broilers have been inconsistent, with positive effects on these characteristics (Mathlouthi et al, 2012;Peng et al, 2016) as opposed to no effects (Alp et al, 2012;Koyama et al, 2014) being detected.…”
Section: Introductionmentioning
confidence: 99%
“…The main components of oregano essential oil (OEO) (Origanum vulgare L.) are carvacrol and thymol, which together represent up to 85% of its composition (Burt, 2004). Oregano essential oil has been associated with antifungal (Bedoya-Serna et al, 2018), antibacterial, and antioxidant activity in vitro (Gandra et al, 2013) and in vivo (Zanini et al, 2013;Ri et al, 2017), stimulation of enzyme secretion (He et al, 2017), and modulation of microbial colonization of the gastrointestinal tract and intestinal morphology (Dias et al, 2015;He et al, 2017). However, reports of its effects on the performance and carcass characteristics of broilers have been inconsistent, with positive effects on these characteristics (Mathlouthi et al, 2012;Peng et al, 2016) as opposed to no effects (Alp et al, 2012;Koyama et al, 2014) being detected.…”
Section: Introductionmentioning
confidence: 99%
“…towards oxidation, heat, and light 9 . Nanoencapsulation seems to be an attractive novel approach to avoid these limitations 10 .…”
mentioning
confidence: 99%
“…These compounds suggest that the fabricated nano‐emulsion exerts high antimicrobial activities. In a similar study, Bedoya‐Serna et al () utilized the PIT method to obtain the oregano essential oil nano‐emulsion and showed that nano‐encapsulated oregano essential oil presented an inhibitory effect against the three genera of fungi ( Cladosporium sp., Fusarium sp., and Penicillium sp.). In another PIT attempt involving cinnamon oil, the formulated nano‐emulsion also exhibited inhibitory activities against a number of foodborne pathogens including Escherichia coli , Salmonella typhimurium , Staphylococcus aureus, and Vibrio parahaemolyticus thanks to the presence of cinnamaldehyde, which was retained in high concentration after emulsification (Chuesiang, Siripatrawan, Sanguandeekul, Yang, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent interest in nano‐emulsion has shifted to optimization of the preparation process of nano‐emulsions containing essential oil, which showed improved bioactivities in comparison with the bare essential oil. Plant materials that were utilized in this process included Salvia multicaulis (Gharenaghadeh et al, ), clove/cinnamon (Zhang, Zhang, Fang, & Liu, ), oregano (Bedoya‐Serna, Dacanal, Fernandes, & Pinho, ), Cleome viscosa (Krishnamoorthy et al, ), and lemon myrtle/anise myrtle (Nirmal, Mereddy, Li, & Sultanbawa, ).…”
Section: Introductionmentioning
confidence: 99%